2017
DOI: 10.1002/adfm.201606572
|View full text |Cite
|
Sign up to set email alerts
|

A Nanoselenium Sponge for Instantaneous Mercury Removal to Undetectable Levels

Abstract: Selective removal of aqueous mercury to levels below 10 ng L−1 or part per trillion remains an elusive goal for public health and environmental agencies. Here, it is shown that a low‐cost nanocomposite sponge prepared by growing selenium (Se) nanomaterials on the surface and throughout the bulk of a polyurethane sponge exhibits a record breaking‐mercury ion (Hg2+) removal rate, regardless of the pH. The exposure of aqueous solutions containing 10 mg L−1–12 ng L−1 Hg2+ to the sponge for a few seconds results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(53 citation statements)
references
References 38 publications
3
50
0
Order By: Relevance
“…Over 75% of the mercury was retrieved in one day (Fig. 1b ), and the efficiency was over 99% after 171 h. This corresponds to 0.35 µg L −1 mercury left in solution, which is well below the acceptable limit in drinking water 14 , 32 . We correlate this with the aforementioned slower inward metal inter-diffusion of mercury once several layers of alloy are formed.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Over 75% of the mercury was retrieved in one day (Fig. 1b ), and the efficiency was over 99% after 171 h. This corresponds to 0.35 µg L −1 mercury left in solution, which is well below the acceptable limit in drinking water 14 , 32 . We correlate this with the aforementioned slower inward metal inter-diffusion of mercury once several layers of alloy are formed.…”
Section: Resultssupporting
confidence: 61%
“…In recent years, other approaches to remove mercury from aqueous streams have been suggested and evaluated 14 18 . Among them is the incorporation of mercury ions in a solid and stable metallic alloy, which is afterwards removed from solution.…”
Section: Introductionmentioning
confidence: 99%
“…However, the binding affinity constant of mercury selenide was one‐million‐fold higher than that of mercury sulfide, while the solubility of the mercury selenide was thousands‐magnitude‐levelly lower . As expected, the equilibrium adsorption capacity of Hg 2+ reached around 0.6 g Hg 2+ g −1 nano‐Se sponge as reported in previous study,[10a] which is much higher than that for MSs. However, it should be noticed that the nano‐Se was well supported on sponge with large surface area.…”
Section: Introductionsupporting
confidence: 81%
“…The as‐formed HgSe was proven to exhibit thousands‐magnitude‐levelly lower solubility compared with that of HgS. [10a] The antioxidant nature of the HgSe also prevents against the mercury neurotoxicity . Moreover, we conducted a leaching experiment to simulate the mercury leaching when the Hg‐laden CuSe‐based sorbents were dumped in environment (shown in Table S4, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“… 41 , 42 It should be noted that Ahmed et al recently reported a nanoselenium sponge that also removes Hg 2+ in seconds. 43 However, they use 30 times more material, and while the nanoselenium sponge does irreversibly bind mercury allowing for easy disposal if used for in-home treatment, 44 , 45 this characteristic might limit its use in wastewater treatment. For Pb 2+ , the fastest material observed, to date, is a porous polymer, mPMF (mesoporous polymelamine-formaldehyde), that reportedly gets below the EPA limit also in seconds; however, the capacity for this material is extremely low, 0.628 mg of Pb 2+ /g, requiring large amounts of sorbent to achieve the same performance as Fe-BTC/PDA ( Table S4 ).…”
Section: Resultsmentioning
confidence: 99%